2023
DOI: 10.1002/pssb.202300112
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field‐Induced Phase Transition on HPX6 (X = C, Si, Ge, Sn) Monolayers

Abstract: Herein, the electronic, thermoelectric, and optical properties of semimetallic HPX6 (X = C, Si, Ge, Sn) monolayers are systematically studied under the influence of external electric field in the framework of density functional theory. A band tuning has been achieved in these structures by the application of an external electric field of appropriate strength. It is predicted that Dirac cone splitting is nearly proportional to the external electric field strength. The modulation of electric properties induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…In essence, the electric field breaks the sublattice symmetry leading to the transformation of the linear bands close to the Fermi level into parabolic ones and an opening of the band gap at the Dirac point occurs. Recently, it has been demonstrated that transverse electric field modulates the electronic properties from semimetallic to semiconducting in buckled HAX 6 (A = N, P, As; X = C, Si, Ge, Sn) monolayers [32,33]. Very recently, Chegel et al studied the fielddependent transport response of TS using a simplified tightbinding (TB) approach [34].…”
Section: Introductionmentioning
confidence: 99%
“…In essence, the electric field breaks the sublattice symmetry leading to the transformation of the linear bands close to the Fermi level into parabolic ones and an opening of the band gap at the Dirac point occurs. Recently, it has been demonstrated that transverse electric field modulates the electronic properties from semimetallic to semiconducting in buckled HAX 6 (A = N, P, As; X = C, Si, Ge, Sn) monolayers [32,33]. Very recently, Chegel et al studied the fielddependent transport response of TS using a simplified tightbinding (TB) approach [34].…”
Section: Introductionmentioning
confidence: 99%